2016
DOI: 10.1016/j.ajpath.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying Pathogenesis of Lewisite-Induced Cutaneous Blistering and Inflammation

Abstract: Lewisite is a potent arsenic-based chemical warfare agent known to induce painful cutaneous inflammation and blistering. Only a few modestly effective antidotes have so far been described in the literature. However, the discovery of effective antidotes for lewisite was hampered by the paucity of the exact molecular mechanism underlying its cutaneous pathogenesis. We investigated the molecular mechanism underlying lewisite-induced cutaneous blistering and inflammation and describe its novel antidotes. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 28 publications
5
72
0
1
Order By: Relevance
“…Ptch1 +/− /SKH-1 is highly sensitive murine model developed in our laboratory to demonstrate the toxic manifestations of environmental agents on the skin 35 . Selection of Ptch1 +/− /SKH-1 hairless mouse strain employed in this study was based on the effects of PAO on cutaneous injury (erythema and edema) in various mouse strains such as FVB, C57BL/6, SKH-1 and Ptch1 +/− /SKH-1 36 . Single application of PAO to Ptch1 +/− /SKH-1 mouse skin caused marked redness within 45 min which became more pronounced with the progression of time.…”
Section: Resultsmentioning
confidence: 99%
“…Ptch1 +/− /SKH-1 is highly sensitive murine model developed in our laboratory to demonstrate the toxic manifestations of environmental agents on the skin 35 . Selection of Ptch1 +/− /SKH-1 hairless mouse strain employed in this study was based on the effects of PAO on cutaneous injury (erythema and edema) in various mouse strains such as FVB, C57BL/6, SKH-1 and Ptch1 +/− /SKH-1 36 . Single application of PAO to Ptch1 +/− /SKH-1 mouse skin caused marked redness within 45 min which became more pronounced with the progression of time.…”
Section: Resultsmentioning
confidence: 99%
“…While investigating the molecular pathogenesis of Lewisite, we recently found that its exposure to murine skin induces activation of the unfolded protein response (UPR) signaling pathway, and blocking UPR signaling with the chemical chaperone 4‐phenylbutyric acid (4‐PBA) protected against Lewisite‐induced skin damage (Fig. ) . Despite an earlier belief that some of the key toxic effects of arsenical vesicants are due to arsenic, the rapidity with which arsenical vesicants act distinguishes the two biological responses and suggests arsenic‐independent mechanisms associated with the exposure to organic arsenicals.…”
Section: Chemical Warfare and Industrial Arsenicalsmentioning
confidence: 99%
“…We recently found that Lewisite induces ROS‐dependent activation of UPR signaling in exposed skin. Thus, treatment with the antioxidant NAC and the chemical chaperone 4‐PBA showed remarkable effects . These agents can decrease UPR signaling and may provide a mechanism‐based intervention against the progression of skin injuries.…”
Section: Countermeasuresmentioning
confidence: 99%
See 2 more Smart Citations